Treating Diabetes Mellitus in Older and Oldest Old Patients - Abbatecola, A.M.; Paolisso, G.; Sinclair, A.J. (Current Pharmaceutical Design, 2015)
There is a rapidly growing number of persons reaching extreme age limits. Indeed, the fastest growth is found in those over the age of 80 years or octogenarians. Along with this continuous rise, there is a significant increase in type 2 diabetes in this population. Unfortunately, individuals living past 80 years of age are often accompanied by numerous comorbidities and geriatric conditions, all which render anti-diabetic treatment options challenging. Indeed the principles of managing type 2 diabetes are similar to younger patients. Special considerations in this delicate group are essential due to the increased prevalence of comorbidities and relative inability to tolerate adverse effects of medication and severe hypoglycemia. It is important to recall that octogenarians have shown to have a greater prevalence for cognitive impairment, physical disability, ren al and hepatic dysfunction, and syndromes, such as frailty compared to younger elders. The frailty syndrome is considered one of the most important limitations when treating octogenarians with type 2 diabetes in polypharmacy. Due to the lack of evidence for specific targets of glucose and glycated hemoglobin (A1C) levels in the elderly, available treatment guidelines are based on data extrapolation from younger adults and expert opinion citing reliable evidence. Overall, the most important conclusion emerging from these groups is to accomplish a moderate glycemic control (A1C levels between 7 -8%) in complex elderly patients. However, the risk of hypoglycemia from some treatments may present the greatest significant barrier to optimal glycemic control for the very old. The present review discusses the highlights from the latest guidelines for treating older persons and underlines the need for specific considerations when treating the very old in order to maintain a balance between treating comorbidities and maintaining quality of life.
Keywords: comorbidities